Tectal Plate Cavernous Malformation—A Rare Cavernoma in Brainstem - Sarkar, Samar C; Amin, Mashah Binte (Journal of Enam Medical College, 2020)
Abstract not available J Enam Med Col 2020; 10(1): 55-57